The Application of Intersection in the Set Theory for Instagram Hashtags - Wakhid Kurniawan; Farha Ramadhan; Hafizd Ardiansyah (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2019)
Technology is developing rapidly with the advent of social media, which paper messages are substitutes for electronic messages that make someone is easier to communicate with others. Many social media exist. The famous ones are Facebook, Instagram, Twitter, and others. With so many social media emerging, every social media must have differences with other social media. Instagram has quite a lot of users, especially in student organizations on campus. The hashtags feature of Instagram makes it is easy to search what to find for people, and group them according to the hashtags used. This paper studies an implementation of intersection operators and applies the intersection operator to classification of Instagram’s hashtags.